Analysis of theoretical approaches to gender pay gap - Grybaitė, Virginija (Journal of Business Economics and Management, 2006)
The number of women in the world labour force is growing. Nevertheless, in spite of women's large share in the labour force, many gender inequities in the labour market, such as gender specific jobs, pay inequities are observed. Women and men do not receive equal pay for equal work. Wage discrimination is reality. Women on average have lower incomes, lower wages and less advantageous terms of employment than men. The purpose of this article is to review main theoretical approaches to the basic economic question about the gender pay gap: why do, women, on average earn less than men. Attention has been focused on basic theoretical approaches: human capital model, labour market discrimination and theory of occupational segregation. The paper is based on empirical data from Lithuania and other European Union countries.First published online: 14 Oct 2010